2020
DOI: 10.1080/02770903.2020.1850768
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of COVID-19 patients with asthma in Wuhan, China: a retrospective cohort study

Abstract: Objective Although it is reported that patients with coronavirus disease 2019 (COVID-19) disease who have comorbidities are at higher risk to suffer adverse clinical outcomes, there are inadequate evidence to clarify the association between COVID-19 and asthma. On this ground, this study aims to systematically analyze the clinical characteristics of COVID-19 patients with asthma. Methods In this single-center, retrospective and observational cohort study, 21 COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
7
0
2
Order By: Relevance
“…Early reports from March 2020 suggested that asthma patients were more likely to have severe COVID-19 requiring intensive care unit (ICU) admission. 5 , 6 Data from the large UK database OPENSafely with data collected from March 2020 to May 2020 showed that those with asthma or COPD taking inhaled corticosteroids (ICS) or oral corticosteroids had higher COVID-19–related mortality than the overall population, but this may have been affected by confounding of the indication for ICS. 7–9 Other large database studies that included patients between February and April 2020 or from March to August 2020, respectively, from the UK or USA, showed that while COPD was a risk factor for mortality in univariate analysis, asthma was not associated with increased death.…”
Section: Introductionmentioning
confidence: 99%
“…Early reports from March 2020 suggested that asthma patients were more likely to have severe COVID-19 requiring intensive care unit (ICU) admission. 5 , 6 Data from the large UK database OPENSafely with data collected from March 2020 to May 2020 showed that those with asthma or COPD taking inhaled corticosteroids (ICS) or oral corticosteroids had higher COVID-19–related mortality than the overall population, but this may have been affected by confounding of the indication for ICS. 7–9 Other large database studies that included patients between February and April 2020 or from March to August 2020, respectively, from the UK or USA, showed that while COPD was a risk factor for mortality in univariate analysis, asthma was not associated with increased death.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed in a study in China, including 21 asthmatics and 100 non‐asthmatic COVID‐19 adult patients who were compared after matching for age, sex, and comorbidity, that the intensive care unit admission rate for COVID‐19 was higher in the asthmatic group 21 . In a study conducted with adult COVID‐19 patients in the United States, the rate of asthma was found to be 14.4% and it was found that being asthmatic or using inhaled steroids, inhaled steroids/long‐acting beta‐agonists, or systemic steroids at the time of diagnosis of COVID‐19 was not associated with the risk of hospitalization 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 114 eligible studies 2 , 3 , 4 , 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ,…”
Section: Tableunclassified